2008
DOI: 10.1002/asi.20939
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the potential of video technologies for collaboration in emergency medical care: Part II. Task performance

Abstract: We are investigating the potential of 3D telepresence, or televideo, technology to support collaboration among geographically separated medical personnel in trauma emergency care situations. 3D telepresence technology has the potential to provide richer visual information than current 2D video conferencing techniques. This may be of benefit in diagnosing and treating patients in emergency situations where specialized medical expertise is not locally available. The experiment with a post-test, between-subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
(32 reference statements)
0
10
0
Order By: Relevance
“…Here, ISRI can be of practical use to identify situations that have positive or negative effects on immersion. This knowledge can help simulation educators to decide the optimal level of different fidelity dimensions [ 20 ] to create adequate and engaging learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…Here, ISRI can be of practical use to identify situations that have positive or negative effects on immersion. This knowledge can help simulation educators to decide the optimal level of different fidelity dimensions [ 20 ] to create adequate and engaging learning environments.…”
Section: Discussionmentioning
confidence: 99%
“…A typical ambulance mission can be divided into a number of defined phases [12,29,30]. Earlier simulation studies of ICT technology for prehospital care [20,22,31] have only focused on one specific phase of the prehospital process, such as on-scene assessment and treatment. It is reasonable to assume that every type of new tool or healthcare technology affects different processes in the overall care chain in different and diverse ways [32].…”
Section: Study Contextmentioning
confidence: 99%
“…Results from previous research in innovation adoption and use (e.g., Rogers, 1995;Venkatesh, Morris, Davis, & Davis, 2003) have consistently shown that when innovations are not perceived as providing advantages over current ways of working, being compatible with existing values and structures, or being easy to try out and use people will not use them unless perhaps there is strong social influence to use the innovation. Our previous research evaluated the potential impact of a new video technology, called 3D medical consultation (3DMC) (Welch et al, 2009), or 3D telepresence, on emergency healthcare Söderholm et al, 2008). In this paper we investigate its propensity for adoption and use in large and small medical centers.…”
Section: Introductionmentioning
confidence: 97%